Exploring the relationship between orthorexia nervosa, mindful eating and guilt and shame - Jessica Thorne; Misba Hussain; Michail Mantzios (Health Psychology Report, 2022)
Background Orthorexia nervosa (ON) is an under-researched maladaptive eating behaviour which focuses on the quality and purity of food. Mindful eating refers to being aware of what we eat by making conscious food choices. Guilt and shame are negative self-evaluative emotions which have been associated with maladaptive eating behaviours. This study explores the relation-ships between ON, mindful eating, and feelings of guilt and shame.